الاستثناء الوارد على مبدأ المساواة بين المتنافسين وفق نظام المنافسات والمشتريات الحكومية الصادر بالمرسوم الملكي م./128 لعام 1440 هـ. - الفراج، أحمد بن سليمان بن أحمد (جامعة القصيم, 2021)
أولى المنظم السعودي عناية بالغة بالعقد الإداري لما تمثله من أهمية على صعيد التنمية والاقتصاد، ولما كانت الشركات والمؤسسات تتنافس فيه بغية الحصول على العقد فقد وضع المنظم مبادئ لتحقيق العدالة بين المتنافسين، ومن هذه المبادئ هو مبدأ المساواة بين المتنافسين في كل مراحل المنافسة. إلا أن المنظم لم يغفل جانب تحفيز ودعم الاقتصاد الوطني في القطاع الخاص ممن حقق المعايير التي نص عليها المنظم، ولأجل أن تدخل في المنافسة فقد وضع لها استثناء خاصا ونص عليه. وكان للمحتوى المحلى والمنشآت الصغيرة والمتوسطة المحلية والمؤسسات الأهلية غير الربحية جانب مهم في دعم الدولة لها من عدة جوانب، ومن تلك الجوانب أن أعطى المنظم تفضيلا سعريا لها على غيرها من المتنافسين، بل إنه أحيانا منع غيرها من الدخول في المنافسة وقصر المنافسة عليها بشروط وضحة. ولذا جاء هذا البحث ليبين هذا الجانب المهم في نظام المنافسات والمشتريات الحكومية الصادر بالمرسوم الملكي رقم م/ 128 بتاريخ 13/11/1440 هـ.
The Saudi regulator paid great attention to the administrative contracts, given the importance they represent in terms of economic development. In addition, the administrative contracts can be considered a target for many companies and institutions that compete with each other to obtain they. In order to maintain a fair competitive environment, the system has established many principles; the most important of which is the equality between competitors in all stages of the competition. However, the regulator has not neglected the aspect of stimulating and supporting the national economy in the private sector who has achieved the standards stipulated by the regulator. Local content, domestic small and medium enterprises, and non-profit organizations have received state support in several aspects. One of the granted aspects is the price preference over other local competitors, as well as the exclusion of any other competitor from entering the competition under clear terms. Therefore, this research came to clarify this important aspect of the Government Tenders and Procurement Law issued by the Royal Decree No. M / 128 dated 11/13/1440 AH.
Keywords: العقود الإدارية -- الصفقات العامة -- القانون الإداري -- المؤسسات الحكومية -- القوانين والتشريعات -- السعودية